Mourning Mandela: sacred drama and digital visuality in Cape Town - Uimonen, Paula (Journal of aesthetics & culture, 2015)
The world united in unprecedented ways in mourning the global icon Nelson Mandela, an emotionally charged historical event in which digital visuality played an influential role. The memorial service for Nelson Mandela on Tuesday, 10 December 2013, gathered dignitaries and celebrities from around the world at the First National Bank Stadium in Johannesburg, to mourn the passing of Madiba and to celebrate his life work. At the Grand Parade in Cape Town, the event was broadcast on large public screens, followed by live music performances and narrowcast interaction with the audience. Building on recent research on public screens during global media events, this article addresses the mediated mourning rituals at the Grand Parade in terms of a sacred drama. Focusing on social relationality, the article discusses how digital visuality mediated a sense of global communitas, thus momentarily overcoming historical frictions between the global north and the global south, while expanding the fame of Madiba. Paying attention to the public display of visual memory objects and the emotional agency of images, it argues that digital visuality mediated social frictions between the living and the dead, while recasting a historical subject as a historical object. The article further discusses how digital visuality mediated cultural frictions of apartheid and xenophobia, through the positioning of Mandela in the pantheon of Pan-African icons, thus underlining the African origin of this global icon. The analysis is based on ethnographic observations and experiences in Cape Town.